2023
DOI: 10.1002/ptr.7713
|View full text |Cite
|
Sign up to set email alerts
|

The phenolic components extracted from mulberry fruits as bioactive compounds against cancer: A review

Abstract: In Asia, mulberry has long been used to treat various infectious and internal ailments as a traditional medication. The compounds found in it have the potential to improve human health. Because there is no approved and defined evaluation procedure, it has not been formally or scientifically recognized. As a result of these investigations, a new frontier in traditional Chinese medicine has opened up, with the possibility of modernization, for the interaction between active components of mulberry and their biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 140 publications
0
8
0
Order By: Relevance
“…A review study revealed that MLE contains various bioactive compounds, including alkaloids, flavonoids, and phenolic acids. 31 Mulberry leaves have strong antioxidant properties and offer several health benefits, including regulation of sugar metabolism, improvement of lipid balance, reduction of oxidative stress, enhancement of mitochondrial function, and protection against diabetes. 10 Additionally, MLE reduces the blood glucose level of individuals with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A review study revealed that MLE contains various bioactive compounds, including alkaloids, flavonoids, and phenolic acids. 31 Mulberry leaves have strong antioxidant properties and offer several health benefits, including regulation of sugar metabolism, improvement of lipid balance, reduction of oxidative stress, enhancement of mitochondrial function, and protection against diabetes. 10 Additionally, MLE reduces the blood glucose level of individuals with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 illustrates a diagram that explains the reasons why ultrasound extraction is considered a technology with great potential. Bioactive compounds are naturally occurring substances in food that can have positive health effects when consumed [ 98 ]. Antioxidants, polyphenols, carotenoids, and flavonoids are some instances of bioactive compounds.…”
Section: The Impact Of Ts On the Bioactive Compounds Present In Foodmentioning
confidence: 99%
“…In recent years, there has been a trend toward the use of plants as sources of various biologically active substances, exerting antioxidant and anti-inflammatory (for example, phenols, anthocyanins, non-anthocyanin flavonoids), anti-carcinogenic (for example, alkaloids, anthocyanins), and anti-diabetic effects [10][11][12]. However, the comprehensive use of a variety of nutrient-rich plants, especially those with fewer culinary and medicinal applications, is still rare, especially in the context of using them as additives in traditional foods.…”
Section: Introductionmentioning
confidence: 99%
“…Mulberry (Morus alba L.) fruits are most popular in East Asian countries such as Korea, China, Japan and Thailand, but are also consumed worldwide [20]. Due to the presence of polyphenols (such as phenolic acids (up to ~30 mg/kg fw), flavanol derivatives (from 55.62 to 432.38 mg/kg fw), and anthocyanins (up to ~3000 mg/kg fw)), polysaccharides, alkaloids, flavonoids, essential amino acids, and vitamins, white mulberry fruits are well known for their health-promoting properties, including anticoagulant, antioxidant, anti-diabetic, anti-obesity, anti-inflammatory, anti-carcinogenic, prokinetic, and neuroprotective effects [12,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%